Assessing Muḥāsabah’s Mediating Function in Generation Z’s Branded Cosmetic Consumption Behavior Patterns - Sukma; Syaparuddin Razak; Andi Ika Fahrika (Jurnal Ekonomi, 2026)
This study examines the mediating role of muḥāsabah in shaping branded cosmetic purchasing habits among Generation Z by integrating the Theory of Planned Behavior and Self-Regulation Theory. Using a quantitative approach and Structural Equation Modeling–Partial Least Squares, the research analyzes the relationships among attitude, subjective norms, intention, muḥāsabah, and purchasing habits. The findings indicate that attitude and subjective norms significantly influence purchase intention, which in turn strongly predicts branded cosmetic purchasing habits. Muḥāsabah exerts an indirect effect by strengthening evaluative attitudes and sensitivity to social norms, thereby reinforcing intention formation. These results suggest that Generation Z consumption behavior is not merely impulsive but reflects a structured decision-making process involving psychological, social, and spiritual reflection. The study contributes to consumer behavior literature by introducing muḥāsabah as a spiritually grounded self-regulatory mechanism within ethical and value-oriented consumption frameworks.